Can Green Finance Promote the Optimization and Upgrading of Industrial Structures?—Based on the Intermediary Perspective of Technological Progress - Wang, Wenjing; Li, Yuexinyi (Frontiers in Environmental Science, 2022)
In the green development context, green finance and industrial structure optimization and upgrading are important parts of green development and a new direction in global development. Based on the relevant data from 31 provinces in China from 2011 to 2020, this study considers the role of green finance in optimizing and upgrading industrial structure from the technological progress perspective. The entropy-weight method and principal component dimension reduction method were used to calculate the green finance development level and industrial structure optimization and upgrading indicators of each province, and the existence of the mediation effect of technological progress was verified by the stepwise regression method, and the Sobel mediation effect test was conducted. Simultaneously, through the comparison of corresponding model construction, it was found that the two-step system GMM is optimal. Further, the corresponding final optimal two-step system GMM model is constructed, which verifies the significant impact of green finance on the optimization and upgrading of industrial structure. The model with the corresponding open to the public, government support, human resources, environmental regulation and urbanization rate control variables, the corresponding control variable optimization and upgrading of industrial structure mainly there is a significant role in promoting.In addition to no significant effect of urbanization rate control variable function, this is due to the urbanization rate of present Chinese corresponding did not bring the optimization and upgrading of industrial structure, it needs improvement and attention. After the robustness test was carried out on the model, regional regression was employed. It revealed that the central green financial role in promoting optimization and upgrading of industrial structure effect is most obvious, and central and western parts of green finance to the optimization and upgrading of the industrial structure is relatively weak in the east, technological progress to promote optimization and upgrading of the industrial structure still exists intermediary role.